(3GdefgGL aj TYH GdEjeGfs - (3CHh YHO Gddg GdMSjf Hf GdMSf Hf eMeO Hf Mdje GdHNGQj GdLQLGfj GdTGaYj, GdMdjej,J (B403 (3g` s
(3BNQgG (B:s
(3GdKGfi YTQ ef GdTYH, aj QLGFg hGdKbI HhYOg, hONd aj gPG GdHGH Gdbhd aj GdOYGA hTQhWg hBOGHg hChbGJg hCMhGdg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B110 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs